Challenges to Asthma Management - Earl Sempio; Saleem Adhami; Saw Win; Tair Nurpeissurn; Syed Munis Ul Hasan; Jahanzeb Kamal Khan; Javed Iqbal; Joseph A Aluoch; Jumaa Bwika; Kenneth Alberca (Journal of the Pakistan Medical Association, 2023)
Despite significant advancements in our understanding of the disease process, the increased morbidity and mortality from asthma may be due in part to inadequate attention being paid to the management of the condition and approaches to improve bronchial asthma control. Data about the difficulties encountered in managing asthma in Low-middle income countries (LMIC) is scarce. The authors aimed to evaluate the challenges faced by each stakeholder in Asthma management. The International Respiratory Forum Conference 2022 commenced in Ho Chi Minh City, Vietnam, including 140 pulmonologists from 11 countries. A survey was conducted using a predesigned structured questionnaire about the challenges faced by each stakeholder (patients, family/caretakers, healthcare professionals, and healthcare policymakers) for Asthma management. Four groups were formed, physicians were randomly divided, and only one section of the questionnaire was distributed among the physicians of each group. Per the physician's perception regarding challenges faced by patients for asthma management, awareness about how to administer the dose or have poor inhaler techniques is usually still being determined. More than 50% believed that there is a need for additional patient education about the day-to-day management of their disease. The cost of therapy was considered the significant barrier faced by the family/caretakers affecting drug adherence. The frequently reported challenge from the physician's end was poor technique use because of poor asthma disease education followed by hurried communication by health care providers to the patients. Around 53% of pulmonologists from the policy maker group reported that the lack of access to affordable quality-assured inhaled medications was the major avoidable barrier that needs to be tackled on the highest priority by the policymakers. This survey has gauged the influence of personal, social, and clinical factors on asthma management and pointed out the gaps regarding adherence from patients' and health professionals' perspectives. The resolutions and inputs suggested providing a practical framework for patient-centered care that treats asthma as an inflammatory disorder and education promoting treatment compliance. Keywords: Asthma Management, Challenges, Developing Countries